In ovo Feeding as a Tool for Improving Performance and Gut Health of Poultry: A Review - Das, Razib; Mishra, Pravin; Jha, Rajesh (Frontiers in Veterinary Science, 2021)
Early growth and development of the gastrointestinal tract are of critical importance to enhance nutrients utilization and optimize the growth of poultry. In the current production system, chicks do not have access to feed for about 48-72 hours during transportation between hatchery and production farms. This lag time affects early nutrient intake, natural exposure to the microbiome, and the initiation of beneficial stimulation of the immune system of chicks. In ovo feeding can provide early nutrients and additives to embryos, stimulate gut microflora and mitigate the adverse effects of starvation during pre-and post-hatch periods. Depending on the interests, the compounds are delivered to the embryo either around day 12 or 17 to 18 of incubation and via air sac or amnion. In ovo applications of bioactive compounds like vaccines, nutrients, antibiotics, prebiotics, probiotics, synbiotics, creatine, follistatin, L-carnitine, CpG oligodeoxynucleotide, growth hormone, polyclonal antimyostatin antibody, peptide YY, insulin-like growth factor-1, etc. have been studied. These compounds affect hatchability, body weight at hatch, physiological functions, immune responses, gut morphology, gut microbiome, production performance, and overall health of birds. However, the route, dose, method, and time of in ovo injection and host factors can cause variation, thereby inconsistencies in results. Studies using this method have manifested the benefits of injection of different single bioactive compounds. But for excelling in poultry production, researchers should precisely know the proper route and time of injection, optimum dose, and effective combination of different compounds. This review paper will provide an insight into current practices and available findings related to in ovo feeding on performance and health parameters of poultry, along with challenges and future perspectives of this technique.